An α2, 3‐Sialyltransferase from Photobacterium phosphoreum with Broad Substrate Scope: Controlling Hydrolytic Activity by Directed Evolution. Issue 50 (7th August 2020) - Mertsch, Alexander; He, Ning; Yi, Dong; Kickstein, Michael; Fessner, Wolf‐Dieter
Abstract: Defined sialoglycoconjugates are important molecular probes for studying the role of sialylated glycans in biological systems. We show that the α2, 3‐sialyltransferase from Photobacterium phosphoreum JT‐ISH‐467 (2, 3SiaTpph ) tolerates a very broad substrate scope for modifications in the sialic acid part, including bulky amide variation, C5/C9 substitution, and C5 stereoinversion. To reduce the enzyme's hydrolytic activity, which erodes the product yield, an extensive structure‐guided mutagenesis study identified three variants that show up to five times higher catalytic efficiency for sialyltransfer, up to ten times lower efficiency for substrate hydrolysis, and drastically reduced product hydrolysis. Variant 2, 3SiaTpph (A151D) displayed the best performance overall in the synthesis of the GM3 trisaccharide (α2, 3‐Neu5Ac‐Lac) from lactose in a one‐pot, two‐enzyme cascade. Our study demonstrates that several complementary solutions can be found to suppress the common problem of undesired hydrolysis activity of microbial GT80 sialyltransferases. The new enzymes are powerful catalysts for the synthesis of a wide variety of complex natural and new‐to‐nature sialoconjugates for biological studies. Abstract : Be tolerant : An engineered sialyltransferase has exceptional tolerance for a wide variety of substrate modifications, both in glycosyl donor and acceptor moieties. Its undesired promiscuous hydrolytic activity was significantly reduced through deep mutational scanning around the active site. The resultant enzyme is a powerful catalyst for the one‐pot cascade synthesis of novel molecular probes for biological studies.